Entre clausura e medo: uma análise semiótica de “Casa Tomada”, de Julio Cortázar - Silva, Edna Aparecida Rodrigues da (2013)
The present work intends to analyse the figurative constructions and passion motivated by fear in the reclusive space, which is constructed in the story “Casa Tomada”, from the book Bestiário, 1951. Taking the methodology of semiotics theory of the French line as a starting point, it is noticed that the discursive mechanisms of enuntiative shifting out and spatial and temporal anchoring are in the construction basis of the meaning of the story, as it describes the daily life of a couple, a brother and a sister, who are shut away in the same house, a family inheritance, which is for them the main scenario and stage of their existences. In the story, the siblings, in a methodical way, gradually leave an exterior existence to live and value the interior of the house. Devoting the greatest part of the day to activities such as tidying the house, the siblings assume a disturbing way of life, since they create a severe system of cleaning and order maintenance of the big house, the only space for conversation of these two solitary adults. The limitation of this solitary suffering is the key point to the subjects’ state of soul, because it is exactly the reclusion that leads to the modal conflict present in the story. It means that the gradation and the reiteration of emotions to which the characters are submitted, reveal an imbalance. Therefore, the characters live a very strict routine devoted exclusively to the house, as if, though inanimate, it had life and were able to determine the actions of the people who lived there. The story is developed under a tone of mystery, creating in its interior a strong feeling of thrilling atmosphere, which arouse affectionate states in the subjects; that is, throughout the story, the main character, the brother, shows signs of his exotic lifestyle, revealing stereotypical behavior – manias, fears, distresses, obsessions – which allow us to think of an isotopy of alienation. This alienation is initially marked by a state of hopelessness, which grows, throughout the story, stronger and stronger, arousing other states created by passion in the subjects. This way, this analysis intends to show how the story enunciator builds his own identity, his sister’s and his own house’s, starting from the coercions of spacetime in which they live, and how the changes in the subjects are directly related to the ideas of alienation and interest, reality andunusual, exterior and interior, which surround all the text.